Up in the air: an examination of the worklife balance of fly-infly-out academics - Jais J.; Smyrnios K.X.; Hoare L.A. (Routledge, 2023)
There is a dearth of research on the worklife balance experiences of academics who undertake short-term international teaching assignments. Academics who teach offshore are also accountable for onshore activities including lecturing, research, supervision of higher degree students, mentoring, publishing and administrative obligations inter alia. These responsibilities pose further challenges to work and life. Within the context of a qualitative design, 11 academics were interviewed in depth regarding their short-term international teaching experiences. Specific issues relating to family separation, excessive work hours, poor assignment planning and lack of organisational recognition were identified. Findings have important implications for academics, and university policy and practice. 2015 HERDSA.